Arogya Chinthamani (ആരോഗ്യചിന്താമണി) - Vallathol Narayana Menon (Vallathol Press, 1976)
Arogya Chinthamani, describing children's treatment in Ayurveda, the Indian system of medicine, written by famous Malayalam Poet Vallathol Narayana Menon. Third edition published on August 1976, printed at Vallathol Press, Cheruthuruthi. Forward by Vaidyaratnam P.S Warrier, Kottakkal. First edition published on March 1904 and second edition in 1925.